Being a Roman Catholic in a context of religious diversity. A «lived religion» exploration among Catholics in Córdoba, Argentina - Rabbia, Hugo Hernán (2017)
From a lived religion approach, the Authors explore how Catholics and ex-Catholics from Córdoba, Argentina, conceive 'being Catholics', and how they react to the plurality of religious options in their everyday lives. The conceptions are diverse and contested. Inter-religious practices are multiple, but when diversity is present within their own homes (inter-religious families) they prefer to avoid speaking of religion.